Self-organized helical superstructure of photonic cellulose loaded with upconversion nanoparticles showing modulated luminescence. Issue 80 (11th August 2016) - Jiang, Haijing; Zhou, Donglei; Qu, Dan; Chu, Guang; Xu, Wen; Song, Hongwei; Xu, Yan
Abstract : Self-organized composite film of chiral nematic cellulose loaded with upconversion nanoparticles whose luminescence can be modulated has been developed. Abstract : The ability to manipulate the color output of nanomaterials is important for applications like optoelectronic devices, light emitting display and lasers. Here, a self-organized helical superstructure of photonic cellulose loaded with upconversion nanoparticles of NaYF4 :Yb, Er has been realized. The modulated upconversion luminescence of the photonic composite film of cellulose-NaYF4 :Yb, Er has been demonstrated with the mechanism proposed.